CULTURE OF RECEIVING POLITICAL INFORMATION IN THE INFORMATION SOCIETY - Haydarov Abror (American Journals, 2023)
This article analyzes the role of information culture, highlighting the role of education, mass media and communications, and the Internet in ensuring personal political security.
Keywords: Information, culture, information society, political security, political culture, mass media.